hw8 - integrating R (1-(1-e-x ) n ) dx by parts. 4.2.7 E (...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon
MATH 471 HW 8 Solutions Pengsheng Ji November 7, 2006 3.8.10 Let N be the number of successes. Then P ( N = k | X = n ) = C n,k p k (1 - p ) n - k for k n , so P ( N = k ) = X n = k P ( N = k | X = n ) P ( X = n ) = X n = k C n,k p k (1 - p ) n - ke - λ λ n n ! = ( λp ) k k ! e - λ X n = k [ λ (1 - p )] n - k ( n - k )! = ( λp ) k k ! e - λp . 3.9.17 The density f - Y ( y ) = λe λy , for y < 0, 0 otherwise so if z > 0, by Formula (7.2) we have f X - Y ( z ) = Z z f X ( x ) f - Y ( z - x ) dx = λ 2 e λx Z z e - 2 λx dx = λ 2 e λx . Since f Z ( - z ) = f Z ( z ), it follows that f Z ( z ) = λe - λ | z | / 2 . 4.1.23 (a) Using Exercise 4.1.20, E ( Y ) = Z 0 e - nx dx = 1 n . (b) The lack of memory property of the exponential implies EZ n = E ( Y + Z n - 1 , so EZ n = 1 /n + EZ n - 1 and EZ n = n k =1 1 /k . The recursion can also be derived by
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 2
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: integrating R (1-(1-e-x ) n ) dx by parts. 4.2.7 E ( 1 X + 1 ) = X n =0 1 n + 1 e- n n ! = e- -1 X n =0 n +1 ( n + 1)! = e- -1 ( e -1) 4.2.8 The generating function of X is r ( z ) = X n =1 z n (1-p ) n-1 p = pz 1-z (1-p ) . Then EX = r ( z ) = p (1-z + zp )-pz (-1 + p ) (1-z + zp ) 2 | z =1 = 1 /p....
View Full Document

This note was uploaded on 09/22/2010 for the course MATH 413 at Cornell University (Engineering School).

Page1 / 2

hw8 - integrating R (1-(1-e-x ) n ) dx by parts. 4.2.7 E (...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online